A comparative needle study: EUS‐FNA procedures using the HD ProCore™ and EchoTip® 22‐gauge needle types. Issue 12 (20th March 2013) - Witt, Benjamin L.; Adler, Douglas G.; Hilden, Kristen; Layfield, Lester J.
<x xml:space="preserve">Abstract</x> The specific needle sizes/types used in performing endoscopic ultrasound‐guided fine needle aspirations (EUS‐FNA) vary. The HD ProCore™ is a 22‐gauge beveled needle allowing for core biopsy along with aspiration material. In this study we compare this needle with a standard 22‐gauge needle. Between April 1, 2011 and November 15, 2011, 18 patients undergoing EUS‐FNA using the HD ProCore™ needle were compared to a control group of 18 cases using the standard 22‐gauge needle. Smears were assessed for: three‐dimensional clusters, thick obscuring clusters, monolayer sheets, cellularity, crowded obscuring single cells, blood, and nuclear staining. Cell blocks were assessed for cellularity and presence of diagnostic material. Records were reviewed for the overall adequacy, number of FNA passes, and patient follow‐up. Overall, the two needle groups demonstrated similar results for the cytology parameters, amount of diagnostic cell block material, adequacy, and accuracy. The mean number of passes to achieve adequacy varied between the groups [2.94 for the standard 22‐gauge needle group versus 2.11 for the beveled needle group (P=0.03)] with no meaningful difference in case duration between needle groups. No complications were reported. The beveled EUS needle affords similar cytologic interpretability, adequacy, diagnostic accuracy, and amount of cell block material as a standard needle. There was a statistically significant trend toward fewer passes to achieve adequacy with the beveled EUS‐FNA needle. Therefore, the EUS‐FNA needle with a lateral bevel is a diagnostically similar alternative to standard endoscopy needles, the possibility that this beveled needle may improve per pass adequacy requires further verification. Diagn. Cytopathol. 2013;41:1069–1074. © 2013 Wiley Periodicals, Inc.